Tuberculosis vaccines update: Is an RNA-based vaccine feasible for tuberculosis? - Sasha E. Larsen; Susan L. Baldwin; Rhea N. Coler (International Journal of Infectious Diseases, 2023)
Objectives: Despite concerted efforts, Mycobacterium tuberculosis (M.tb), the pathogen that causes tuberculosis (TB), continues to be a burden on global health, regaining its dubious distinction in 2022 as the world's biggest infectious killer with global COVID-19 deaths steadily declining. The complex nature of M.tb, coupled with different pathogenic stages, has highlighted the need for the development of novel immunization approaches to combat this ancient infectious agent. Intensive efforts over the last couple of decades have identified alternative approaches to improve upon traditional vaccines that are based on killed pathogens, live attenuated agents, or subunit recombinant antigens formulated with adjuvants. Massive funding and rapid advances in RNA-based vaccines for immunization have recently transformed the possibility of protecting global populations from viral pathogens, such as SARS-CoV-2. Similar efforts to combat bacterial pathogens such as M.tb have been significantly slower to implement. Methods: In this review, we discuss the application of a novel replicating RNA (repRNA)-based vaccine formulated and delivered in nanostructured lipids. Results: Our preclinical data are the first to report that RNA platforms are a viable system for TB vaccines and should be pursued with high-priority M.tb antigens containing cluster of differentiation (CD4+) and CD8+ T-cell epitopes. Conclusion: This RNA vaccine shows promise for use against intracellular bacteria such as M.tb as demonstrated by the feasibility of construction, enhanced induction of cell-mediated and humoral immune responses, and improved bacterial burden outcomes in in vivo aerosol-challenged preclinical TB models.